A Implementasi Kelelahan Dan Beban Kerja Pegawai Dalam Meningkatkan Komitmen Organisasi - Mappamiring Mappamiring; Zulfikry Sukarno (Institute Agama Islam Negeri (IAIN) Sultan Amai Gorontalo, 2024)
Human resources are one of the resources owned by the company that can be used to achieve goals. Human resources are different from other resources because humans have thoughts and feelings that can be distinguished from other components. Thus, the background of this research problem is whether work fatigue or workload is more dominant in affecting the organizational commitment of fire fighting employees in Makassar City. The purpose of this study was to find out whether both affect the organizational commitment of firefighters. Primary data were collected from Makassar City Fire Department employees, who were then used as respondents using the slovin formula after calculation, so the researchers adjusted 67 respondents. The assumptions of normality, multicolonicity, and heteroscedasticity have been used to test the results of primary data collected through questionnaire distribution. Data analysis was performed using descriptive and inferential statistical analysis. All hypotheses are acceptable because the results show that workload and work burnout, both partially, have not significant effect on organizational commitment. With an adjustable square value of R of 72.9%, we can find that the work fatigue variable affects 4% of the employee organizational commitment variable, and the workload variable affects 27.1% of other variables not described in this study